REVITALIZING OLD BANTEN: EVIDENCE ON EFFECTIVENESS AND POLICY OUTCOMES - Ramadhaningsih Ramadhaningsih; Titi Stiawati (Jurnal Kebijakan Publik, 2026)
The Old Banten area is a historical and religious heritage site that reflects the legacy of the Banten Sultanate and plays a strategic role in cultural and religious tourism in Banten Province. To address the physical degradation of the heritage site, limited infrastructure, and unmanaged socio-economic activities, the Banten Provincial Government and the Serang City Government implemented a revitalization program from 2018 to 2021. This study aims to analyze the effectiveness of the Old Banten revitalization program after its implementation and to identify obstacles that influence its results. This study uses a descriptive qualitative approach, with data collected through interviews, field observations, and document analysis. Informants were selected purposively and included representatives from government agencies, heritage managers, cultural heritage conservators, traders, and tourists. Data analysis was conducted using the effectiveness framework proposed by Nakamura and Smallwood, which includes the achievement of program objectives, efficiency, target group satisfaction, client response, and maintenance systems. The findings indicate that the revitalization has been effective in improving the physical condition and visual quality of the core zone, contributing to increased tourist visits. However, the program's objectives are not yet uniformly understood across institutions, and the benefits of revitalization have not been distributed equitably, particularly in terms of socio-economic impacts on local merchants. Utilization of supporting facilities remains suboptimal, coordination between institutions is limited, and the maintenance system is fragmented. Overall, the revitalization has demonstrated partial effectiveness, achieving physical improvements but facing challenges in integrating governance, community participation, and sustainable management of cultural heritage areas.